Correction: HIV retesting for pregnant and breastfeeding women across maternal child health services in Nampula, Mozambique. - Chloe A Teasdale; Michelle Choy; Fatima Tsiouris; Eduarda Pimentel De Gusmao; Etelvino C P Banqueiro; Aleny Couto; Kwalila Tibana; Nicole Flowers; Marilena Urso; Mirriah Vitale; Elaine J Abrams (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0283558.].